2012
DOI: 10.5120/9301-3519
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of User Requirements Gathering Practices in Agile and Non-Agile Software Development Team

Abstract: Software engineering is continuously gaining success day by day. In last decades a lot of growth has been observed in the software industry. Various new software development methodologies are introduced such as agile software development with increasing demand of software industry. In all these development methodologies, user requirements play an important role for completion of the successful project. If requirements are not clear it can be the reason of project failure. Now a day's some industries are not aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Capturing right requirements and requirements right can be an issue and one of the factor of the failure of many software development projects. Ghai and Kaur (2012) found that 37% of the problems occurred in the development of challenging systems are related to the requirement specification phase. Therefore requirement engineering is an important activity of the project because it can uncover and analyzes various future problems which can become a cause of failure of the software project Ghai and Kaur (2012).…”
Section: Exposure Of Land Information System (Lis) From Literature Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Capturing right requirements and requirements right can be an issue and one of the factor of the failure of many software development projects. Ghai and Kaur (2012) found that 37% of the problems occurred in the development of challenging systems are related to the requirement specification phase. Therefore requirement engineering is an important activity of the project because it can uncover and analyzes various future problems which can become a cause of failure of the software project Ghai and Kaur (2012).…”
Section: Exposure Of Land Information System (Lis) From Literature Re...mentioning
confidence: 99%
“…Getting the requirements right and getting the right requirements can mean the difference between a successful projects one that satisfies the needs of its users and is delivered on time and on budget and one that fails Nevo Technologies (2004). Analysis by Ghai and Kaur (2012) shows that 37% of the problems occurred in the development of challenging systems are due to the requirement specification.…”
Section: Introductionmentioning
confidence: 99%